On understanding the material removal mechanism when cutting Ceramic Matrix Composites (CMCs) - Gavalda Diaz, Oriol (2018)
The continuous increase in Turbine Entry Temperature (TET) in aerospace gas-turbines is the main driving force behind research efforts in the development of Ceramic Matrix Composites CMCs. Among different ceramic composites, SiC-based \CMCs are the material choice for aero-engine manufacturers for employment in structural components of turbines such as seal segments and turbine blades/vanes. Hence, because of their non-oxide ceramic nature and their exposure to harsh environments (i.e. high temperatures and stresses), the risk of these materials to suffer environmental degradation is a matter of concern for the aerospace industry. Consequently, the importance of understanding the state of the CMCs surface (e.g. cracks or residual stresses) after the manufacturing processes is of critical importance to achieve the desired life in service. Hence, as CMCs components need some machining operations to achieve the final features and dimensions, this thesis focuses on understanding the material removal mechanism and its effects on the machined surface. Moreover, because of the unique nature of SiC-based CMCs (i.e. orthotropic, brittle, hard and heterogeneous) its machining process becomes very challenging, especially when drilling small holes, and for this reason hole-making has been chosen as a target operation.